Produção e customização na construção volumétrica offsite: estudos de caso no Reino Unido - Ferreira, Tamiris Capellaro (2024)
Offsite volumetric construction makes it possible to carry out a greater number of activities in the factory, reducing work time on site, as a potential way of improving construction efficiency. Over the years, the adoption of offsite volumetric construction has seen only marginal increases, due, among other things, to the negative perceptions of many customers, which are related to the high degree of standardization necessary to reduce unit costs in economies of scale. In this context, considering how the characteristics of the production used by an offsite volumetric construction company can influence its approach to customization is fundamental. Thus, it is in the relationship between the different production characteristics adopted by offsite volumetric construction companies and their strategy for offering customization that the research gap in this work lies. Understanding this relationship is also of great practical relevance, since some companies may not be able to remain in the market because they do not adequately link the production system used with the level of customization they wish to offer to customers. Furthermore, this work has academic relevance in the area of knowledge of offsite volumetric construction. Its main objective is to propose a model that relates production characteristics to customization strategies in offsite volumetric construction companies. To develop the model, the main strategy used was multiple case studies in six English offsite volumetric construction companies. The model helps to understand the relationship between the different production characteristics adopted by offsite volumetric construction companies and the way they offer customization. It can help not only new companies to appropriately choose the customization strategies to the production characteristics they adopt, in order to be competitive in the market, but also companies that are in transition processes between customization strategies or between production characteristics to understand which are the design and production requirements that increase their chances of success in the market.